Transcendence / Mohd Zamri Azizan - Azizan, Mohd Zamri (Faculty of Art and Design, 2021)
From ancient times to the present, people who believe in the existence of God have inhabited the world. Even the current statistics also show that the number of gods’ believers around the world such as Islam, Christianity, Hinduism, Buddhism and so on is still far exceeding the number of those who are not having any faith. Taking Malaysia as an example, Belief in God is the first pillar of the Rukunegara. The existence of Allah and HIS blessings are eternity. Nothing precedes HIS existence, greatness, majesty, and the existence of Allah lasts forever. Praise be to Allah who is endowed with all the attributes of perfection. HE is the one who initiates the creation of beings and restores them. HE does whatever HE wants. HE is the owner of the glorious authority and the proprietor of a very severe torment, as well as the guide of the chosen servant to the straight path.The interpretation of this work gives more awareness to remember Allah in any agenda of life other than inviting people to return to their original axis again which is increasingly careless with oneself. Disasters after disasters have hit the global world recently and most current is the emergence of the Covid-19 virus which allows humans to re-think to find their own faults and try to return to our creator.